PSYCHOLOGICAL PROBLEMS OF SUICIDES AND SUICIDE ATTEMPTS OF SERVICEMEN IN THE ARMY OF REPUBLIC OF ARMENIA - Vardanyan , A. R. (Արդի հոգեբանություն, 2019)
Taking into account the expression of the quantitative indicator of suicides in the Armed Forces of the Republic of Armenia and the need to develop measures to prevent them, this article discusses such features and patterns that are based on the results of forensic psychological examinations and research on factors contributing to suicide. The implementation of such examinations and the generalization of the main motives for suicide and attempted suicide of military personnel can contribute to a systematic and focused work on effective means of preventing the suicide of military personnel.